Implementation of Smart Indonesia Card (KIP) Policy in Poverty Alleviation in Maros Regency - Andi Aslinda; Umi Kalsum; Andi Cudai Nur (Jurnal Aktor, 2024)
This study aims to determine the implementation of local government policies in poverty reduction in Maros Regency through the Smart Indonesia Card (KIP). This research uses a qualitative approach and produces descriptive data. Data collection is done by observation, interviews and documentation. Data is processed using interactive model analysis, namely data condensation, data presentation and conclusion testing. The focus of this research is based on the policy implementation model proposed by George C Edward III. 4 (four) variables that affect policy implementation, namely communication, resources, disposition and bureaucratic structure. Based on the results of the research obtained, it can be concluded that the Maros Regency Social Office has implemented and implemented the Smart Indonesia Card (KIP) policy as an effort to overcome poverty in Maros Regency. To measure the implementation using four indicators, namely 1). Communication, Communication is considered very important in policy implementation, in the context of communication there are three things that are considered, namely a) Information, regarding the implementation of the KIP policy has been made by the government as the President's flagship program in overcoming poverty in Maros Regency through the transmission of delegations given through the Regent of Maros to the Social Service, b) Clarity, communication received by KIP implementers must be clear and not confusing. c) Consistently, Maros district social service employees must be consistent in implementing the KIP smart Indonesia card policy. 2) Resources, sources that support effective policies, namely a) staff, employees who handle KIP participants are still lacking, b) information, employees in the Maros Regency Social Service must know what to do in the future through information submitted by superiors, c) the authority runs through the Maros Regency Social Service Government in terms of implementing the KIP smart Indonesia Card policy. d) facilities, advice and infrastructure in the Maros Regency Social Office, especially in the Smart Indonesia Card policy program, the KIP still lacks supporting facilities in carrying out duties, 3) Disposition, has been carried out well by the government and stakeholders as evidenced by various kinds of support and supervision.4) bureaucratic structure, factors that have an influence on the policy implementation process, namely a) bureaucratic structure,  The existing structure in the Maros Regency Social Office has been made based on the main duties and functions of each, b) Standard Operating SOP procedures, the Maros Regency Social Office already has clear SOPs and clear organizational structures as well.